Using new digital technologies in high school during the war in Ukraine - Tverdokhliebova, Natalia; Yevtushenko, Nataliia (My University, 2023)
The purpose of the work is to analyze the understanding of the mechanism of action of artificial intelligence in the educational process of a higher school.
Keywords: digital technologies; high school; artificial intelligence systems